Detection and identification of fungi causing strawberry wilt disease in North Sumatra, Indonesia - Safni, Irda; Simanjuntak, Cadrak Perdamenta (Universitas Lampung, 2025)
Strawberry (Fragaria sp.) is primarily grown in temperate and some subtropical countries. With the expansion of fruit commodities in Indonesia, including the introduction of foreign cultivar, strawberry has been increasingly cultivated locally. In North Sumatra, strawberry cultivation, mainly for agritourism, is concentrated in Karo Regency, Berastagi District. This study aimed to detect and identify fungi responsible for wilt disease in strawberry plants across several areas of Berastagi, North Sumatra. This research was conducted from July 2022 to May 2023 at the Plant Disease Laboratory, Faculty of Agriculture, Universitas Sumatera Utara. The study followed Koch’s postulates: the pathogen was isolated and purified from symptomatic plants, then inoculated into healthy plants. Infected plants exhibiting the same symptoms as the initial sample were subsequently re-isolated, purified, and identified at the molecular level. The results confirmed that the causal agent of wilt disease in Daulu (Rini Colia Strawberry, Esy Azera Strawberry) and Dolat Raya (Sonakmalela Strawberry, Alea Strawberry, Sembiring Gurky Strawberry) was Fusarium oxysporum.